Novel on-line twist extrusion process for bulk magnesium alloys. (15th November 2019) - She, J.; Peng, P.; Tang, A.T.; Zhang, J.Y.; Mao, J.J.; Liu, T.T.; Zhou, S.B.; Wang, Y.; Pan, F.S.
Abstract: This study presented a novel intense plastic straining process called on-line twist extrusion (OLTE). An on-line torsional strain was applied on magnesium extruded rod during extrusion. After OLTE, the grains are refined from the periphery to the center of the bar, and the refined extent can be promoted with increased torsion speed. A fully recrystallized ultrafine grained structures and spiral shaped basal texture with the average grain size of 1.2 μm are successfully achieved with increased torsion speed. The microstructure evolution and strengthening mechanism were also discussed. Graphical abstract: Unlabelled Image Highlights: A novel intense plastic straining process (OLTE) has been developed. A spiral shaped basal texture is successfully achieved. The grains are refined from the periphery to the center with increased torsion speed.